Unconventional monetary policy expansion: the economic impact through a dynamic CGE model. (2018) - Socci, Claudio; Severini, Francesca; Pretaroli, Rosita; Ahmed, Irfan; Ciaschini, Clio
The ongoing economic stagnation and low inflation rates affecting EU have refuelled the debate on the role and the limits of monetary policy in pushing the economic growth. Given the tight margins for fiscal policy for EU state members, traditional and unconventional monetary policies are becoming more looked-for to break out of this condition. However, the main issue on whether the real or nominal aspects prevails still remains. In this situation, a framework able to identify and analyse any interaction between economic and financial flows becomes crucial to detect the dynamics pushing towards expansions or contractions resulting from monetary policies. Therefore, the aim of this paper is to investigate the direct and indirect impact of monetary policies implemented by the European Central Bank on the main Italian macroeconomic variables both in aggregate and disaggregate terms. For this purpose we use dynamic computable general equilibrium (CGE) model calibrated on the financial social accounting matrix for Italian economy.